Factors Affecting the Financial Literacy of Students in Bhaktapur District - Raut, Babloo Kumar; Twanabasu, Sunita (Bagiswori Journal, 2024)
Financial literacy is the ability to make wise financial decisions. It is crucial for college students who are starting to make financial decisions and prepare for the working world. In this regard, this paper aims to examine the status of financial literacy of students studying management in community colleges. This study is based on primary data collected from 308 management students of six community colleges of Bhaktapur District. SPSS was used to derive results via descriptive analysis, correlation analysis, and regression analysis in order to achieve study aims. The average financial literacy score indicates that students are not totally literate. Pearson correlation result indicates that the age of the person affects the financial knowledge of an individual. However, gender and family income of respondents do not have a significant impact on respondents’ financial literacy. The results show that financial attitude, financial behavior, and financial knowledge all have a significant contribution to the level of financial literacy. Therefore, it is important for students to have financial knowledge, financial judgment and money matters. Thus improvements should be made throughout their academic careers. Financial education in college will enable students to become responsible and rational members of society.